Association of Gestational Age with Postpartum Hemorrhage: An International Cohort Study. (June 2021) - Butwick, Alexander J.; Liu, Can; Guo, Nan; Bentley, Jason; Main, Elliot K.; Mayo, Jonathan A.; Shaw, Gary M.; Stephansson, Olof
Abstract : Background: Risk factors for postpartum hemorrhage, such as chorioamnionitis and multiple gestation, have been identified in previous epidemiologic studies. However, existing data describing the association between gestational age at delivery and postpartum hemorrhage are conflicting. The aim of this study was to assess the association between gestational age at delivery and postpartum hemorrhage. Methods: The authors conducted a population-based retrospective cohort study of women who underwent live birth delivery in Sweden between 2014 and 2017 and in California between 2011 and 2015. The primary exposure was gestational age at delivery. The primary outcome was postpartum hemorrhage, classified using International Classification of Diseases, Ninth Revision—Clinical Modification codes for California births and a blood loss greater than 1, 000 ml for Swedish births. The authors accounted for demographic and obstetric factors as potential confounders in the analyses. Results: The incidences of postpartum hemorrhage in Sweden (23, 323/328, 729; 7.1%) and in California (66, 583/2, 079, 637; 3.2%) were not comparable. In Sweden and California, the incidence of postpartum hemorrhage was highest for deliveries between 41 and 42 weeks' gestation (7, 186/75, 539 [9.5%] and 8, 921/160, 267 [5.6%], respectively). Compared to deliveries between 37 and 38 weeks, deliveries between 41 and 42 weeks had the highest adjusted odds of postpartum hemorrhage (1.62 [95% CI, 1.56 to 1.69] in Sweden and 2.04 [95% CI, 1.98 to 2.09] in California). In both cohorts, the authors observed a nonlinear (J-shaped) association between gestational age and postpartum hemorrhage risk, with 39 weeks as the nadir. In the sensitivity analyses, similar findings were observed among cesarean deliveries only, when postpartum hemorrhage was classified only by International Classification of Diseases, Tenth Revision—Clinical Modification codes, and after excluding women with abnormal placentation disorders. Conclusions: The postpartum hemorrhage incidence in Sweden and California was not comparable. When assessing a woman's risk for postpartum hemorrhage, clinicians should be aware of the heightened odds in women who deliver between 41 and 42 weeks' gestation. Abstract : In a retrospective analysis of childbirth registries in California and Sweden, the incidence of postpartum hemorrhage varied from 3.2 to 7.1%. Compared to delivery at a gestational age of 37 to 38 weeks, delivery at 41 to 42 weeks was associated with a doubling of risk among parturients in California and a 62% increase in Swedish women.Supplemental Digital Content is available in the text.